2011
DOI: 10.1002/ceat.201100034
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption during Vacuum Microwave Treatment of Potato Starch: A Phenomenological Model

Abstract: It is known that the water binding capacity of starch increases after vacuum microwave treatment. Microwave radiation absorbed by the starch sample affects its sensible, latent internal and chemical (bond and conformational) energy levels. A phenomenological model was developed based on energy sinks in starch, practically described as increasing temperature, breaking bonds between water and amylopectin/amylose molecules, changing the phase of water from liquid to vapor and structural rearrangements at short (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…Dyrek et al (2007) found that irradiation of corn and potato starches with microwaves (440 and 800 W) for 10-15 min generated two types of radicals that were similar to those generated by conventional heating of the starches at 210 • C for 30 min. Mollekopf et al (2011a,b), Treppe et al (2011), andDixit et al (2011) studied vacuum microwave (460, 500, 600, 750, 1,000, and 1,500 W) treatment of potato starch (18% moisture; 30-600 s) and found that the starch's water-binding capacity increased. Both granule shrinking and slight cracking of the granule surface occurred, and the granules became less crystalline; however, for the most part, birefringence remained.…”
Section: Microwave Heatingmentioning
confidence: 96%
“…Dyrek et al (2007) found that irradiation of corn and potato starches with microwaves (440 and 800 W) for 10-15 min generated two types of radicals that were similar to those generated by conventional heating of the starches at 210 • C for 30 min. Mollekopf et al (2011a,b), Treppe et al (2011), andDixit et al (2011) studied vacuum microwave (460, 500, 600, 750, 1,000, and 1,500 W) treatment of potato starch (18% moisture; 30-600 s) and found that the starch's water-binding capacity increased. Both granule shrinking and slight cracking of the granule surface occurred, and the granules became less crystalline; however, for the most part, birefringence remained.…”
Section: Microwave Heatingmentioning
confidence: 96%
“…B. Monoethanolamin (MEA), Diethanolamin (DEA) oder Diglykolamin (DGA) angewendet. Insbesondere letzteres erscheint für die Reinigung von Biogas auf Biomethan, dessen Produktionsmengen in den kommenden Jahren deutlich ausgebaut werden, vielversprechend . Es kann als wässrige Lösung sehr hochkonzentriert vorliegen und weist dadurch auch bei atmosphärischem Druck eine hohe Differenz in der CO 2 ‐Beladung zwischen Absorptions‐ und Desorptionsbedingungen auf, woraus geringe Waschmittelumlaufraten resultieren.…”
Section: Introductionunclassified